RADEC Learning Model as an Alternative in Chemistry Learning: A Literature Study - Nofita, Agnes (Edukimia, 2024)
The purpose of this study was to identify the effect of applying the RADEC learning model on shaping the profile of Pancasila students, learning outcomes, critical thinking skills, creative thinking skills, independence in learning, understanding of chemical multirepresentations, and understanding of concepts. This research is a literature review using data from research journal articles published in 2020-2023. Articles were collected using google scholar and researchGate with the keywords RADEC learning model and chemistry so that nine articles were analyzed. Based on the results of the analysis, it is known that the RADEC learning model can be applied to Voltaic cells, reaction rates, electrolyte and non-electrolyte solutions, atomic structure, buffer solutions and colloids. In addition, the application of this learning model can shape the profile of Pancasila students, critical thinking skills, creative thinking skills, and understanding of multirepresentation of chemistry.